Kratka etnografija rab mobilnega telefona v Sloveniji - Kotnik, Vlado (Javnost (Ljubljana), 2007)
The use of mobile phone is, so to say, an inevitable social phenomenon incorporated into the everyday life of human race in the transition from the twentieth to twenty-first century. This article aims to reveal how the mobile phones' users perceive their appurtenance to global context of the "mobile reality", how this kind of technology determines or structures the organisation of people's everyday life, and what is the attitude of mobile phones' users towards their personal uses of mobile phone. To examine the above-mentioned fields, we have to understand the social uses as cultural practices which use the ideologies of consumption and utopian dreams to produce the "technologised mobile identities" and new forms of communication. Anthropology offers an epistemological apparatus which can be used, on the micro level, to shed some light upon some aspects of this global process whichwe are facing today. This article presents an ethnographic case study of the uses of mobile phone in Slovenia.
Keywords: komuniciranje; communication; medosebne komunikacije; mobilni telefoni; družbeno vedenje; fashion; moda; vsakdanje življenje; zasebnost; privacy